ANALISA PENGARUH PENGELUARAN PEMERINTAH DI SEKTOR PENDIDIKAN DAN KESEHATAN TERHADAP INDEKS PEMBANGUNAN MANUSIA PROVINSI KALIMANTAN SELATAN - MUHAMMAD NOR (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research was conducted to learn and analyze the impact of government expenditure on education sector and health sectorto the human development index of South Kalimantan Province.            This research uses panel in five years of time period, from 2013 to 2017. The data processing is done using the fixed effect model (FEM) method. This approach is a regression technique that produces a constant value or different equation intercept for each cross section that is fixed in time series. Generalization process on the fixed effect approach, is done by entering the dummy variable into the regression equation that made a difference in the intercept value.            The results of this research proved that a significant correlationbetween the government expenditure on education sector and health sector and the human development index in South Kalimantan Province. However, the impact of government expenditures on the education sector is negative, which means that the government expenditure on the education sector will decrease onthe human development index in the Province of South Kalimantan. However, the impact of the government expenditures on the health sector is significant and positive, which means that the government expenditure on the health sector will raise the human development index in South Kalimantan Province. The result was based on t-test.Keyword : Government expenditures in the education sector, Government expenditures in the health sector, Human development index.